Pelimpahan Kekuasaan Dalam Jual Beli Tanah Kavling Tanpa Sertifikat Prespektif Hukum Ekonomi Syariah - Marisa Natasya; Siti Rochmiyatun (CV. Doki Course and Training, 2024)
Delegation of power states that the transfer, delegation, or granting of a mandate carried out by one person to another. In this delegation of power, problems often occur due to irresponsible parties. Therefore, this study formulates the main problem as follows: how is the delegation of power in the sale and purchase of land plots without certificates on Jalan Taqwa Mata Merah, Palembang. The purpose of this study is to examine the delegation of power in the sale and purchase of land plots without certificates from the perspective of Sharia Economic Law. This study is an empirical legal study. Data sources consist of primary data and secondary data. Primary data were obtained through interviews with informants. The results of the study indicate that problems in the delegation of power in the sale and purchase of land plots without certificates occur because they are carried out verbally. This delegation of power in the perspective of Sharia Economic Law is called the wakalah bil ujrah contract to obtain. The delegation of power that occurred in this case is not in accordance with the wakalah bil ujrah contract and is detrimental to the parties in the sale and purchase of land plots.